Muhammad : A Biography of the Prophet - Armstrong, Karen (London Weidenfeld & Nicolson, 2001)
A life of the prophet Muhammad by bestselling religious writer Karen Armstrong.
Include Bibliography and Index
Keywords: Islam -- Muslims -- Islam and state